2020
DOI: 10.1111/jre.12826
|View full text |Cite
|
Sign up to set email alerts
|

Oral microbiota and atherothrombotic carotid plaque vulnerability in periodontitis patients. A cross‐sectional study

Abstract: Background An increased risk of atherothrombotic vascular events has been reported in periodontitis patients. Periodontitis is associated with dysbiotic subgingival biofilms and bacteremia. Objective We hypothesized (a) that the oral microbiome is associated with the carotid microbiome and (b) that periodontitis could contribute to plaque vulnerability. The aim of this study was to determine the associations between periodontitis, the carotid microbiome, and the local innate immune response in carotid atheroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
0
13
0
1
Order By: Relevance
“…46 Therefore, the increased angiogenesis of EPCs caused by P. gingivalis LPS may shed light on the clinical associations of periodontitis with atherosclerotic plaque vulnerability. 47,48 Nevertheless, the clinical relevance of this study is limited due to its in vitro design and needs to be interpreted with caution. In vivo studies are highly warranted to investigate the mechanistic role of EPCs in the linkage between periodontitis and atherosclerosis at different stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Therefore, the increased angiogenesis of EPCs caused by P. gingivalis LPS may shed light on the clinical associations of periodontitis with atherosclerotic plaque vulnerability. 47,48 Nevertheless, the clinical relevance of this study is limited due to its in vitro design and needs to be interpreted with caution. In vivo studies are highly warranted to investigate the mechanistic role of EPCs in the linkage between periodontitis and atherosclerosis at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…The progressive function of EPCs is considered a contributing factor for the expansion and vulnerability of atherosclerotic plaque and subsequent atherosclerotic complications like hemorrhage, rupture, and thrombosis 46 . Therefore, the increased angiogenesis of EPCs caused by P. gingivalis LPS may shed light on the clinical associations of periodontitis with atherosclerotic plaque vulnerability 47,48 . Nevertheless, the clinical relevance of this study is limited due to its in vitro design and needs to be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…The Human Oral Microbiome Database provides a list and detailed description of the features and genomic information of the currently known oral cavity bacteria [32,33]. The main constituents of the oral microbiota are bacteria [4,34]. The oral bacterial community consists of six main phyla-Firmicutes, Bacteroidetes, Proteobacteria, Actinobacteria, Spirochaetes, and Fusobacteria-which account for 94% of the taxa detected.…”
Section: Oral Microbiomementioning
confidence: 99%
“…It has been observed that the microbiota of healthy individuals can present up to 101 species of fungi. Candida species are the most common, followed by Cladosporium, Aureobasidium, Saccharomyces, Aspergillus, Fusarium, and Cryptococcus [11,34].…”
Section: Oral Microbiomementioning
confidence: 99%
“…Similarly, Isoshima et al [ 51 ] used pyrosequence of 16S rRNA pyrosequencing to show that the majority families of the periodontal bacteria were Burkholderiales , Bacillale , and Rhizobiales , forming the soil bacterial family. Utilizing the techniques of microbial whole-genome sequencing, Brun et al [ 52 ] and Koren et al [ 53 ] showed that the most dominantly detected phyla of periopathogens in APs with periodontitis were Proteobacteria , Actinobacteria , Firmicutes , and Bacteroidetes . Current studies aiming to detect a variety of periodontal microorganisms in atherosclerotic and subgingival plaques obtained different results due to the differences in study cohorts selected, DNA detection techniques, and periodontal sample collection.…”
Section: Periodontal Microbial Signature Of Atherosclerotic Plaquesmentioning
confidence: 99%